The effect of materials and design on the reliability of through-glass vias for 2.5 D integrated circuits: a numerical study. Issue 2 (24th October 2020) - Ahmed, Omar; Okoro, Chukwudi; Pollard, Scott; Jiang, Tengfei
Abstract : Purpose: This study aims to investigate the factors responsible for substrate cracking reliability problem in through-glass vias (TGVs), which are critical components for glass-based 2.5 D integration. Design/methodology/approach: Numerical models were used to examine the driving force for substrate cracking in glass interposers due to stress coupling during heating. An analytical solution was used to demonstrate how the energy release rate (ERR) for the glass substrate cracking is affected by the via design and the mismatch in thermal strain. Then, the numerical models were implemented to investigate the design factors effects, such as the pitch distance, via diameter, via pattern, via design, effect from a stress buffer layer and the interposer materials selection on the susceptibility to substrate cracking. Findings: ERR for substrate cracking was found to be directly proportional to the via diameter and the thermal mismatch strain. When a via pattern is implemented for high-density integration, a coupling in the stress fields was identified. This coupling effect was found to depend on the pitch distance, the position of the vias, and the via arrangement, suggesting a via pattern-dependent reliability behavior for glass interposers. Changing the design of the via to an annular shape or a substrate-cored via was found to be a promising approach to reduce the susceptibility to substrate cracking compared to a fully filled solid via. Also, the use of a stress buffer layer, an encouraging design prospect presented for the first time for TGVs in this study, was found to significantly reduce cracking. Finally, alternative via and substrate materials showed lower tendency for substrate cracking, indicating that the reliability of glass interposers can be further enhanced with the implementation of such new materials. Originality/value: This study signifies the first attempt to comprehensively evaluate the susceptibility to crack formation in glass interposers during heating. Therefore, this study provides new perspectives on how to achieve a significant potential reliability improvement for TGVs.